Government Policies in Implementing Social Welfare for National Development - Kasmawati, Andi; Sailan, Manan; ., Bakhtiar (KnE Social Sciences, 2024)
This study evaluates the welfare state model applied in the development of Indonesia and the relevance of the welfare state concept in developing Indonesian policies. The method used is qualitative research, and the research object is government policies utilized in the application of the welfare state concept (welefar staat) in the forms of documents, books, and journals, as well as research results. Secondary data in the form of documents, laws and regulations, references/books, journals, and other supporting documents were obtained by researchers from existing sources in the literature. . Data were recorded and materials were systematically analyzed. Data analysis was done in the form of a clear and concrete description of the objects discussed qualitatively. Results show that the Indonesian government separates model categories in running a welfare state, namely the old-age security program and the healthcare program. This means that state administrators (government) must continuously strive to achieve the welfare of their citizens. This is a constitutional mandate that cannot be simply ignored, so it is impossible for state administrators to escape it. Keywords: government policy, social welfare, national development